OPTIMIZATION OF TECHNOLOGICAL PARAMETERS OF HYDRAGENERATION PROCESS OF ACETYLENE USING A PILOT CATALYTIC PLANT - Tanirbergenova Sandugash Kudaibergenovna; Тugelbayeva Dildara Abdikadyrovna; Erezhep Nurzay (Academic Scientific Journal of Chemistry, 2020)
A pilot plant was launched and the modes of acetylene hydrogenation on cobalt catalysts were worked out. It has been found that the modified 7% Co/ SiAl cobalt catalyst is active in the process of hydrogenating acetylene into ethylene. Optimal conditions of acetylene hydrogenation on 7% Co/ SiAl catalyst were determined. The effects of temperature, space velocity and the ratio of initial components in the hydrogenation of acetylene to ethylene were investigated. The textural characteristics of cobalt catalysts before and after the hydrogenation of acetylene were investigated by the SEM method. The structure of cobalt catalysts after the hydrogenation of acetylene does not lose catalytic activity and selectivity. It has been found that catalyst samples have channels of different sizes, flaky particles and fibers located in the gaps between large aggregates are also present on the surface. The optimum temperature was 180 ° C in the hydrogenation of acetylene into ethylene at conversion 73.0%. Conversion of acetylene increases to 81.2% when temperature rises to 200°C, acetylene conversion decreases to 68% with further temperature exceeding to 220°C. Acetylene conversion again increases from 68 to 73.6% at 140°C in the ratio of acetylene to hydrogen 1:2. The selectivity of the catalyst 7%Co/SiAl to ethylene was studied depending on the temperature in the acetylene hydrogenation reaction. The selectivity to ethylene decreases with increasing temperature, since an increase in temperature activates side reactions.